2005
DOI: 10.1158/1078-0432.ccr-05-0449
|View full text |Cite
|
Sign up to set email alerts
|

High Thioredoxin Expression Is Associated with Resistance to Docetaxel in Primary Breast Cancer

Abstract: Purpose: Thioredoxin overexpression is suggested to be associated with resistance to several chemotherapeutic agents in vitro. In the present study, it has been studied whether or not high thioredoxin expression is associated with resistance to docetaxel therapy in breast cancer patients. Patients and Methods: Sixty-three primary breast cancer patients were treated with docetaxel (60 mg/m 2 , q3w) for four cycles in the neoadjuvant setting. Expression of thioredoxin, estrogen receptor (ER), p53, BRCA-1, and Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
117
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 38 publications
3
117
1
1
Order By: Relevance
“…Stathmin1 stimulates microtubule depolymerization and interferes with taxane binding to b-tubulin subunits (26). This process is also obstructed by thioredoxin by interfering with the redox regulation of tubulin cysteine residues, which microtubule assembly depends on (29). It has been shown that thioredoxin expression increases in tumors after docetaxel treatment (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stathmin1 stimulates microtubule depolymerization and interferes with taxane binding to b-tubulin subunits (26). This process is also obstructed by thioredoxin by interfering with the redox regulation of tubulin cysteine residues, which microtubule assembly depends on (29). It has been shown that thioredoxin expression increases in tumors after docetaxel treatment (29).…”
Section: Discussionmentioning
confidence: 99%
“…This process is also obstructed by thioredoxin by interfering with the redox regulation of tubulin cysteine residues, which microtubule assembly depends on (29). It has been shown that thioredoxin expression increases in tumors after docetaxel treatment (29). In chemoresistant (HeyA8-MDR) tumors, we found that intermittent 1Â/wk therapy leads to an upregulation of b-tubulinIII, stathmin1, and thioredoxin relative to controls and/or continuous chemotherapy and an upregulation of b-tubulinIII and stathmin1 was observed in chemosensitive (HeyA8) tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thioredoxin system is often overexpressed in many cancer cells (5,6), and TrxR deficiency or transfection with dominant-negative mutant Trx leads to a retardation in tumor progression and metastasis (7)(8)(9). In addition, high Trx expression is associated with the resistance to tumor chemotherapy (10,11) and results in increased tumor angiogenesis (12). Supported by these observations, the thioredoxin system has been emerging as an important target for cancer treatment.…”
mentioning
confidence: 99%
“…The TrxR-Trx system is thought to have key functions in cancer cell proliferation. A number of reports have shown that the Trx-TrxR system has an important role in tumor growth and resistance to chemotherapeutic agents in many malignant neoplasms (22), i.e., prostate (23), pancreas (24), breast (25), non-small cell lung cancers (26), and malignant mesothelioma (27). Previous studies also reported that TrxR1 was one of the genes strongly associated with tumor proliferation in some cancers (23,28).…”
Section: Discussionmentioning
confidence: 99%